A Game of Thrones : A Song of Ice and Fire #1 - Martin, George R. R. (New York : Bantam Books, 2011)
The kingdom of the royal Stark family faces its ultimate challenge in the onset of a generation-long winter, the poisonous plots of the rival Lannisters, the emergence of the Neverborn demons, and the arrival of barbarian hordes.
Reprint. Originally published: 1996.
Keywords: Fantasy fiction